Radiation Pollution in Cancer and other Diseases Using some Immunological and Clinical Parameters: Weam Saad Al-Hamadany1 , Dhuha S. Saleh2 , Muthana A. Shanshal3 - Al-Hamadany, Weam Saad (The Iraqi Journal of Veterinary Medicine, 2012)
There was a noticeable increase in cancers, congenital malformations, spontaneousabortion and other cases among Iraqi population after both Gulf Wars I and II, the presentstudy aimed to the detection and determination of internal radiation pollution with DepletedUranium (DU), and investigate the effects of this type of radiation exposure on someimmunological parameters for the first time in Iraq. A total of 88 blood samples werecollected from 45 patients and 43 healthy persons during 2009-2010; from the outpatients ofthe Institute and Hospital of Radiotherapy and Nuclear Medicine and Al-Kadhymia TeachingHospital in Baghdad. Results: 1. Contaminated persons with DU were 48 persons (54.5%)from total 88 persons. 2. The places (Al-Taji, Abu-Graib, Al-Hurriyah, New Baghdad and AlSader town) recorded 44.7% of contaminated persons. 3. Effects of internal contaminationwith DU; chronic radiation exposure; influenced by the dose and personal susceptibility, thusit caused significant decrease in Eosinophils% and Lymphocytes %, Hb%, NBT+ % and mostof IFN-γ levels, while there was some elevation in Basophiles%. 4. IL-2 levels did notaffected by chronic exposure by DU. But it was affected by acute exposure to radiation sinceits levels elevated significantly in radiation occupationals blood.Conclusions: Radiationpollution as internal contamination with U and DU is a public health problem. It might be thepredisposing factor for the cases under focus since it caused immunosuppression by affectingimmune cells in number or function comparing with the non-contaminated.